Cost-effectiveness of video-observed therapy for ambulatory management of active tuberculosis during the COVID-19 pandemic in a high-income country - Fekadu, Ginenus; Jiang, Xinchan; Yao, Jiaqi; You, Joyce H.S. (International journal of infectious diseases, 2021)
•The USA is a high-income country with a low tuberculosis (TB) burden.•The coronavirus disease 2019 pandemic suspended directly observed therapy (DOT) for patients with TB.•Suspension of DOT worsened treatment outcomes and increased the cost of TB.•Video-observed therapy was cost-effective for TB during the pandemic in the USA. The coronavirus 2019 (COVID-19) pandemic caused suspension of directly observed therapy (DOT) for patients with active tuberculosis (TB). This study aimed to estimate the outcomes of pandemic-related DOT suspension and the cost-effectiveness of video-observed therapy (VOT) during the pandemic. A decision-analytic model was constructed to project outcomes of adult patients with active TB from the perspective of a US healthcare provider. Two model-based analyses were conducted: (1) before (with DOT) and during [with self-administered therapy (SAT)] the pandemic; and (2) VOT vs SAT during the pandemic. The primary outcome measures were direct medical costs and disability-adjusted life years (DALYs). In the base-case analysis, care during the pandemic (with SAT) increased the cost (by US$285 per patient) and DALYs (by 0.2155 per patient) in comparison with DOT. Care with VOT reduced DALYs (by 0.4870) and costs (by US$1797) in comparison with SAT. On probabilistic sensitivity analysis, care during the pandemic (with SAT) increased DALYs in 100% of 10,000 simulations, and increased costs in 55.52% of instances. Care with VOT reduced DALYs and costs in 99.7% and 68.79% of instances, respectively. The probability of VOT being cost-effective was 99.4% at the willingness-to-pay threshold of 50,000 US$/DALY. Suspension of DOT during the COVID-19 pandemic worsened treatment outcomes. VOT was found to be a cost-effective option for active TB care in an outpatient setting.